2018
DOI: 10.1080/20786190.2018.1504866
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the medical internship programme at King Edward VIII hospital, South Africa in 2016

Abstract: Background: In 2005, the Health Professions Council of South Africa (HPCSA) extended the duration of the internship programme to ensure that all young medical graduates are adequately prepared to work at a district hospital during their year of community service. King Edward VIII hospital (KEH) is an HPCSA accredited training hospital, which has been training interns for many years. The aim of this study was to assess intern perceptions of their training at the hospital. Methods: This cross-sectional, descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
1
13
0
1
Order By: Relevance
“…Intern’s welfare not met was seen as the first challenge echoed by the interns whereby they have expressed the need for accommodation, delay employment contracts and work without pay. The findings of this study were convenient to the other studies whom have reported that lacking the right support and having poor infrastructure that is not conducive for the wellbeing of the IDs brings disturbance to their learning [ 23 , 26 , 27 ]. Likewise, other studies have stated that when there is poor support in; hospital management, medical intern doctor’s welfare, hospital staff, and academic opportunities, it greatly impacts an ID’s transitional phase from being a medical student to becoming a registered doctor [ 24 , 28 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Intern’s welfare not met was seen as the first challenge echoed by the interns whereby they have expressed the need for accommodation, delay employment contracts and work without pay. The findings of this study were convenient to the other studies whom have reported that lacking the right support and having poor infrastructure that is not conducive for the wellbeing of the IDs brings disturbance to their learning [ 23 , 26 , 27 ]. Likewise, other studies have stated that when there is poor support in; hospital management, medical intern doctor’s welfare, hospital staff, and academic opportunities, it greatly impacts an ID’s transitional phase from being a medical student to becoming a registered doctor [ 24 , 28 ].…”
Section: Discussionsupporting
confidence: 79%
“…Rigor in this study was observed according to the Lincoln and Guba strategies of credibility, dependability, confirmability and transferability [ 21 ]. Whereby in-depth interview questions as data collection tool were derived and formulated out from the previous academic sources and studies [ 22 , 23 ]. All participants were informed about the aim of study by telephone or email one week before conducting interviews.…”
Section: Methodsmentioning
confidence: 99%
“…To gain a better picture of this topic we recommend the use of additional tools on safety or safety climate as transforming organizational culture may be critical to improving patient outcomes. Also noteworthy for LMICs there should be questions on pay and remuneration, as together with infrastructure and resource adequacy these factors are commonly cited as reasons for poor internship experience [61].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Reid (2018) reported a lack of standardised guidelines for the implementation of the CSP from the National Department of Health within the South African context. The infrastructural inadequacies including poor supervision and large caseloads in public hospitals contributed to a growing dissatisfaction with the structure of the CSP (Ross, Naidoo, & Dlamini, 2018;Van Niekerk, 2012). The available literature on the CSP in South Africa (Khan et al, 2009;Reid, 2018;Ross et al, 2018;Van Niekerk, 2012) does not seem to discuss the significance of, and the need to standardise the minimum competencies for graduates to be certified as independent practitioners at the end of the CSP, particularly in audiology.…”
Section: Introductionmentioning
confidence: 99%
“…The infrastructural inadequacies including poor supervision and large caseloads in public hospitals contributed to a growing dissatisfaction with the structure of the CSP (Ross, Naidoo, & Dlamini, 2018;Van Niekerk, 2012). The available literature on the CSP in South Africa (Khan et al, 2009;Reid, 2018;Ross et al, 2018;Van Niekerk, 2012) does not seem to discuss the significance of, and the need to standardise the minimum competencies for graduates to be certified as independent practitioners at the end of the CSP, particularly in audiology. The key soft and hard skills, attitudes and knowledge required for audiologists to be considered fit for independent practice seems unclear and predominantly overlooked (Reid, 2018).…”
Section: Introductionmentioning
confidence: 99%